ECO-CITIES: UE NET Systems Integration as New Paradigm Shift in Sustainable Energy Generation and Utilization - Amakpah, Steve-Wonder; Liu, Gengyuan (Journal of Environmental Accounting and Management, 2026)
Cities are responsible for approximately three-quarters of the world’s energy consumption, so they play a major role in energy issues such as economic security and climate change. To contribute to the limited literature on advanced energy research such as UE NET and eco-cities energy systems in China, this research investigates the energy system of Qingdao Eco-park. It explores the efficiency of an emerging energy system, Ubiquitous Energy Internet (simply called UE NET) Technology and its application in eco-cities as the new paradigm shift in energy generation and utilization towards achieving sustainable development. Published data on environment and energy indicators for example carbon emission intensity, energy consumption and the final project proposals of Qingdao Eco-park on the energy potential of UE NET were scientifically analyzed. Results indicate that UE NET technology system has a high power saving potential than any stand-alone energy generation options. Energy awareness enables new sets of interactive energy-saving behaviors where devices control their power state to meet user needs while minimizing energy use (Lanzisera et al., 2014). This assertion does not only support findings of this research in a broader perspective, but specifically calls for “energy-integration” that is not just new but very efficient. To achieve this, including low carbon emission intensity reduction, a rigorous further research on UE NET technology in China with full policy-maker support is highly recommended.